2022
DOI: 10.3389/fimmu.2022.936196
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk Between Liver Sinusoidal Endothelial Cells and Hepatic Microenvironment in NASH Related Liver Fibrosis

Abstract: Chronic liver injury can be caused by many factors, including virus infection, alcohol intake, cholestasis and abnormal fat accumulation. Nonalcoholic steatohepatitis (NASH) has become the main cause of liver fibrosis worldwide. Recently, more and more evidences show that hepatic microenvironment is involved in the pathophysiological process of liver fibrosis induced by NASH. Hepatic microenvironment consists of various types of cells and intercellular crosstalk among different cells in the liver sinusoids. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 149 publications
(197 reference statements)
0
7
0
Order By: Relevance
“…Fibrosis activates the HSC by releasing cytokines and chemokines, leading to the recruitment of immune cells to the damaged area. [23][24][25] Moreover, cell adhesion molecules (CAMs), such as intercellular adhesion molecule-1 (Icam-1) and vascular cell adhesion molecule-1 (Vcam-1), are expressed in the HSCs. [26][27][28][29] Recent studies have also demonstrated the upregulation of Icam-1 and Vcam-1 in NASH mouse models.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrosis activates the HSC by releasing cytokines and chemokines, leading to the recruitment of immune cells to the damaged area. [23][24][25] Moreover, cell adhesion molecules (CAMs), such as intercellular adhesion molecule-1 (Icam-1) and vascular cell adhesion molecule-1 (Vcam-1), are expressed in the HSCs. [26][27][28][29] Recent studies have also demonstrated the upregulation of Icam-1 and Vcam-1 in NASH mouse models.…”
Section: Resultsmentioning
confidence: 99%
“…The premise of the hepatobiliary clearance pathway is that foreign objects can enter the perisinusoidal space from the hepatic sinusoid and be absorbed by hepatocytes. The hepatic sinusoidal window is 100~150 nm 210 , only smaller foreign matters (< 100 nm) can pass through the hepatobiliary clearance pathway. Moreover, due to the negative charge on the surface of the hepatocytes, the positively charged intrusions can promote hepatobiliary clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of fenestration of LSECS protects the liver from ongoing damage by limiting toxins to specific areas ( 19 ). However, the formation of a continuous basement membrane lining the sinusoids disrupts the bidirectional exchange of oxygen and nutrients between hepatocytes and sinusoids ( 51 ), as well as the lipoprotein secretion of hepatocytes and the de novo lipogenesis in hepatocytes which aggravates hepatic steatosis in NASH ( 52 ). LSECs can also secrete Wnt and hepatocyte growth factor (HGF), which together act as key hepatocyte mitogens with a potent liver regenerative capacity that is readily switched to a pro-fibrotic phenotype, in which the Erk1/2/Akt axis in LSECs acts as a switch ( 53 ).…”
Section: Changes In Crosstalk Of Lsecs In Hepatic Microenvironmentmentioning
confidence: 99%
“…KCs and infiltrating macrophages can usually be divided into two subtypes, including M1 macrophages, which produce proinflammatory cytokines such as TNF-α, IL-1b, CCL2 and CCL5, and M2 macrophages which secrete a distinct set of mediators including IL-13, IL-10, IL-4 and TGF-b ( 58 , 59 ). Imbalance of M1/M2 ratio may be the key to the progression of NASH to liver fibrosis ( 52 ). Pro-inflammatory KCs may also produce cytokines and chemokines which increase the expression of adhesion molecules by LSECs, leading to leukocyte infiltration and activation ( 60 ).…”
Section: Changes In Crosstalk Of Lsecs In Hepatic Microenvironmentmentioning
confidence: 99%